Influence of Plastic Waste Fibers on the Strength of Lime-Rice Husk Ash Stabilized Clay Soil - A. S. Muntohar (Institute of Research and Community Outreach - Petra Christian University, 2009)
A study has been undertaken to investigate the strength of stabilized clay-soil reinforced with randomly distributed discrete plastic waste fibers by carrying out unconfined compressive strength and tensile-split strength test. In this study, the clay soil was stabilized with lime and rice husk ash mixtures. The effect of the fiber length and content on the compressive and split tensile strength was investigated. The laboratory investigation results show that inclusion of the plastic waste fiber increased significantly both the unconfined compressive strength and tensile-split strength of the stabilized clay soil. The fiber length plays a significant contribution in increasing the soil strength. To contribute for any significant improvement on compression as well as tensile strength, the fiber length should be in range of 20 mm to 40 mm. Fiber reinforcements also reduced soil brittleness by providing smaller loss of post-peak strength.